Cybercrime - Hudak, Heather C. (Abdo Publishing, 2019)
Computer networks allow people to easily share information. Organizations and entire cities rely on computer networks. Hackers can break into networks to disrupt systems or steal data. Hacking and other cybercrimes are on the rise. Cybercrime explores common cybercrimes and how people can guard against these threats.